Design of a Natural Draft Biochar Reactor for Sustainable Biomass Waste Management in Rural Areas - Karlvin, Jungan (Universiti Malaysia Sarawak, 2022)
Existing localized biochar reactors are typically economical for producing biochar. However, it requires experience, skill, and labor to operate and maintain the reactor. This research developed a novel biochar reactor design, combining the Top-lit Updraft (TLUD) gasifier and double barrel retort concepts to simplify the operation and maintenance of the reactor. At the same time, it reliably produces biochar safe for treating water. The pilot-scale study involved experimenting with various configurations of the chimney, air inlet opening, and feedstock using a 23 cm (L) x 23 cm (W) x 70 cm (H) reactor model to understand the effect on the combustion performance and biochar yield. The full-scale study involved further investigation of the effect of the chimney on the combustion process and biochar yield in a 1.3 m (L) x 1.3 m (W) x 1.5 m (H) full-scale reactor to finalize the biochar reactor design. The laboratory-scale study involved the determination of suitable precursors by pyrolyzing various precursors under controlled conditions to determine the biochar yield, followed by analyzing the physicochemical and adsorption characteristics. The pilot-scale study showed that the chimney D:H ratio affected the draft of the reactor (which subsequently affected the temperature profile), primary and secondary air openings were essential to achieve complete combustion of feedstock and volatile gas, respectively, and feedstock affected the combustion temperature and duration as range favorable for pyrolysis of biochar is between 600 and 900 °C for about 60 to 90 min respectively. A 0.2 m (dia) x 1.5 m (H) chimney showed the best performance in regulating fuel combustion, achieving uniform pyrolytic temperature distribution, and consistent pyrolytic conditions for producing biochar in smokeless emission. A series of physicochemical characterization and adsorption studies showed bamboo was a suitable precursor for producing biochar, mainly attributed to the consistent biochar yield averagely of 30% (high lignin content), high surface area and porosity, well-developed and homogeneous microscopes structure, carbon content above 60%, and favorable adsorption capacity. The development of this novel biochar reactor has enabled the rural area community to manage their agriculture waste sustainably.